2019
DOI: 10.1038/s41598-019-46682-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging of Actin Turnover Parses Early Stem Cell Lineage Divergence and Senescence

Abstract: This study describes a new approach to discern early divergence in stem cell lineage progression via temporal dynamics of the cytoskeletal protein, F-actin. The approach involves real-time labeling of human mesenchymal stem cells (MSCs) and longitudinal tracking of the turnover dynamics of a fluorogenic F-actin specific probe, SiR-actin (SA). Cells cultured in media with distinct lineage factors and labeled with SA showed lineage specific reduction in the actin turnover shortly after adipogenic (few minutes) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Previous confocal studies with fixed tissues showed that the actin cytoskeleton undergoes dramatic rearrangements as cells damaged by Plasmodium invasion are extruded from the midgut epithelial layer, by forming an actin ring at the base of damaged cells that is gradually constricted ( 1 ). Because traditional actin markers, such as phalloidin, are highly toxic ( 11 ) and impermeable to live cells, we decided to use the F-actin-specific SiR-actin fluorophore ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous confocal studies with fixed tissues showed that the actin cytoskeleton undergoes dramatic rearrangements as cells damaged by Plasmodium invasion are extruded from the midgut epithelial layer, by forming an actin ring at the base of damaged cells that is gradually constricted ( 1 ). Because traditional actin markers, such as phalloidin, are highly toxic ( 11 ) and impermeable to live cells, we decided to use the F-actin-specific SiR-actin fluorophore ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the abovementioned markers, new tools and approaches have been proposed to monitor MSC aging such as SiR-actin, a fluorogenic F-actin specific probe that can be used to evaluate actin turnover (Mishra et al, 2019). CyBC9 (another fluorescent probe) combined with high-throughput screening revealed accumulation of mitochondria in senescent MSCs that presumably resulted from the loss of membrane potential (Ang et al, 2019).…”
Section: Strategies For Monitoring Msc Senescencementioning
confidence: 99%
“…Notably, various biological processes such as proliferation [10] and differentiation [11,12] are influenced by cell shape. In addition, actin cytoskeleton-mediated cell shape changes have been shown to be vital for the regulation of MSC lineage commitment [13].…”
Section: Actin Propertiesmentioning
confidence: 99%